Dispositional Coping Strategies as Factors Explaining Various Aspects of Teachers' Well-being - Agnieszka Buczak (Ignatianum University Press, 2024)
Objectives  of  the  research: The aim of the study was to explain various aspects of teachers' well-being through their ability to use personal resources, such as strategies for coping with stress. Research  methods: The research survey was completed by 382 teachers from the Lublin Voivodeship. An original tool, the Teacher's Well-Being Scale (TWS), with satisfactory psychometric properties, was used. Additionally, the Satisfaction with Life Scale (SWLS) and the Brief COPE Inventory were used. To explain the relationship between various dimensions of teachers' well-being and coping strategies as an explanatory variable, a canonical analysis was carried out. A short description of the context of the issue: The role and profession of a teacher are associated with numerous stressors and difficult situations that may impact teachers' well-being. Research findings: Teachers' active approach to dealing with difficult and problematic situations and avoiding the strategy of denial promotes well-being related to the their work (especially in the dimensions of social relations and self-fulfillment). It is also important for life satisfaction in areas unrelated to the professional role of teachers. Coping strategies based on acceptance and seeking social support promote life satisfaction and professional well-being among teachers, who note satisfactory conditions at school for work and professional and personal development. Conclusions and/or recommendations: Research showing links between coping skills and the well-being of teachers and their students would be interesting. The current research results on teachers' well-being explained by their self-efficacy and coping skills seem satisfactory. However, they do not correspond with the disturbingly limited research on student well-being, school satisfaction, and the results of teachers' work.